Pattern of Musculoskeletal Disorders in Adult Diabetics patient (Bangladesh Medical Journal, 2019)
Diabetes mellitus is associated with several musculoskeletal (MSK) disorders. Due to increased incidence and life expectancy causes increased prevalence and clinical importance of MSK alterations in diabetic subjects. It is difficult to find out the direct relation with metabolic control. This study was conducted to explore the pattern of musculoskeletal disorders in the diabetic patients. A cross-sectional study was conducted from January' 2016 to June' 2016 at Department of Physical Medicine and Rehabilitation, Bangabandhu Sheikh Mujib Medical University, Dhaka with 190 cases divided in two groups. Patients aged 40-70 years with musculoskeletal disorder with diabetes mellitus (type 2) for five years attending in the department of Physical Medicine and Rehabilitation were included in group A. Patients with MSK disorder without diabetes aged 40- 70 years were included in group B. Main outcome measures were done by Chi square test and unpaired t test were calculated by using SPSS-20. Out of 190 patients, more than half (53.68%) patients were belonged to age 51- 60 years in group A and 49(51.58%) in group B. Majority (56.84%) patients were female in group A and 43(45.26%) in group B. Twenty three (24.21%) patients were house wives in group A and 25(26.32%) in group B. Fifty two (54.73%) patients had osteoarthritis of knee in group A and 26(27.36%) in group B. Twenty one (22.11%) patients had frozen shoulder in group A and 9(9.47%) in group B. Sixteen (16.84%) patients had Flexor tenosynovitis in group A and 04(4.21%) in group B. Fifteen (15.78%) patients had Fibromyalgia in group A and 05(5.26%) in group B. Twelve (12.63%) patients had Planter fascities in group A and 03(3.16%) in group B. Which were statistically significant (p0.05) between two groups. More than half patients were belonged to age 51-60 years and female were predominate in both groups. Common musculoskeletal disorders in diabetic patients were osteoarthritis of knee, frozen shoulder, Flexor tenosynovitis, Fibromyalgia, Planter fascities, Rheumatoid arthritis, Carpel tunnel syndrome, Lumbar spondylosis, Cervicalspondylosis and DISH. This study will also be helpful for different organizations working in this area including physiatrist in their program for delivering a comprehensive treatment service. As a result patients were more benefited.Bangladesh Med J. 2019 Jan; 48 (1): 5-12